A method of pre-design estimate with adjustment for alternative specifications and price escalation - Lim, Lee Tong; Ueda, Tamon; Jearkjirm, Vithool; Ping Kunawatsatit; The Government of Australia (Bangkok : Asian Institute of Technology, 1988)
Numerous methods had been developed in the past to estimate the cost of a construction project in the predesign stages. None of them has provided sensitivity analysis for the magnitude of changes in the project cost if there are alternatives in the specifications of the construction materials, or there exist price escalations for construction materials and labor cost in the market. This study has d eve loped an estimating model by finding the correlations of magnitudes of work s and the floor areas of the buildings as well as the correlation s of the floor areas a nd t he project sizes. These correl ations are collected from past informations of proj ects that had be e n compl eted or under construction. Apartme nt building projects are studi ed and works of the projects are grouped into 25 work items. The results are tested with new projects a nd are proved to be reasonably accurate.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1988
Keywords: Building materials; Building -- Contracts and specifications